THE INFLUENCE OF ORGANIZATIONAL CULTURE AND OCCUPATIONAL HEALTH AND SAFETY (OHS) IMPLEMENTATION ON EMPLOYEE PERFORMANCE AT PT BUKIT ASAM TBK - Rahmawati, Nindy Merry; Oktaviannur, M; Barusman, M. Yusuf Sulfarano (Program Studi Magister Manajemen, 2024)
This study aims to analyze the influence of organizational culture and the implementation of Occupational Health and Safety (OHS) on employee performance at PT Bukit Asam Tbk, Tarahan Port Unit. A quantitative approach was employed using a survey method, with data collected through questionnaires distributed to 116 respondents. The research instruments were tested for validity and reliability. Data analysis techniques included multiple linear regression, with t-tests, F-tests, and the coefficient of determination analyzed using SPSS version 29. The results reveal that both organizational culture and OHS implementation have a significant and positive impact on employee performance, both partially and simultaneously. The coefficient of determination value of 97.4% indicates that the two independent variables dominantly explain employee performance, with the remaining 2.6% influenced by other factors not examined in this study. These findings suggest that improving organizational culture and optimizing the implementation of OHS are crucial strategies for enhancing employee performance within the company.